Contrato de trabalho intermitente no Brasil e na Itália : estudo comparado sob a perspectiva do princípio constitucional do valor social do trabalho - Souza, Jessica Alves de (2023)
The historical conjunction of fixed-term employment contracts in Italian and Brazilian labor law is consistent with a global trend toward the flexibilization of labor relations. This phenomenon entails a series of mechanisms developed primarily with the aim of curbing unemployment and informality in the labor market, which poses a blatant challenge to Human Rights. Efforts to address this issue are justified, in particular, by the introduction of labor reform, highlighting its importance in the field of work once its social value is understood and protected by Human Rights, rendering it a fundamental element of individual and collective identity. Exposing how problematic the violation of constitutional principles around labor rights is underscores the scientific and social relevance of addressing the regulation of fixed-term employment in Brazil and Italy, given recognition of the growing need for a clearer and more objective discussion on workers’ dignity and the social value of labor. This paper will approach the issue from the perspective of a comparative study with Italian legislation, revealing possible gaps between fixed-term employment contracts and the Brazilian Constitution. The proposed hypothesis is that the Brazilian contract modality is an instrument for precarious labor resulting from the global trend of devaluation of workers. The goal is to determine whether there is a violation of constitutional rights that leads to unconstitutionality. In this sense, the correlations between fixed-term employment contracts in Brazil and Italy will be outlined through a constitutional interpretation of the aforementioned principles, starting from the premise of an international protection framework that prevails over the national system, as well as the use of comparative analysis. The bibliographical research, which uses reasoning of the indirect documentation type, presents historical and statistical data through techniques of textual analysis and comparison of legal systems. The conclusion is that labor reform, due to its obvious scientific and social relevance, as well as the economic considerations that guide it – especially when it comes to fixed-term contracts, given their importance in the work sphere – leads to violations of constitutional principles that pervade debates on legislation in Brazil and Italy, being exposed as an insufficient tool to promote dignified labor.